THE ROLE OF DYSPHEMISMS IN THE POETIC TEXT - Yodgorov Hamid (Scholar Express Journal, 2022)
In world linguistics, since the beginning of the 20th century, attention has been paid to studying the issues of linguopoetics. In the process of researching problems, linguopoetics is developing together with fields such as text linguistics, pragmatic linguistics, linguostylistics and cognitive linguistics
Keywords: linguistics; linguostylistics and cognitive linguistics; pragmatic; cognitive